Some Chemical Components of Lactarius pyragalus from Diverse Locations - PEKSEN, AYSUN; YAKUPOGLU, GOKCEN; KIBAR, BEYHAN (Asian Journal of Chemistry, 2010)
The aim of this study was to determine pH, moisture, ash, nitrogen, protein and mineral contents in mushroom samples of Lactarius pyragalus collected from different locations in some districts and villages of Samsun and Ordu provinces at Middle Black Sea Region of Turkey. Some chemical components of fresh L. pyragalus samples are as follows: pH 5.95, moisture 68.74 %; ash 1.13 %, N 0.71 % and protein 4.42 %. Mean mineral contents (mg kg-1) of L. pyragalus samples were found to be: P 100.96, K 3510.37, Ca 87.27, Fe 52.38, Mg 301.48, Na 154.43, Zn 40.64, Cu 9.01 and Mn 4.68. Significant differences were found among locations for other chemical properties of L. pyragalus with the exception of Ca, Na and Mn contents.